RESPONSE KONSUMEN TERHADAP ASOSIASI ENDORSER PERUSAHAAN - Andreas Ari Sukoco; Fadjar Iriantono (Jurnal Riset Manajemen dan Bisnis, 2010)
The issue of advertising effectiveness is strongly related with theinstrumental attributes of an advertisement. One of the attributes is an endorser. The existence of an endorser has a big influence on the outcomes of an advertising activity because an endorser has a strong effect on the image of products or services advertised. This inquiry merely focuses on the attempt to see the impact of an endorser image on the image of products being advertised. It is also to see how the changes of the image of an endorser and the decision making made by a top management about a problematic endorser have relevance with customers’ perspectives. The participants of this study are the students of Duta Wacana Christian University. The analysis is with different test average, mean, and standard deviation. The result indicates that the presence of a celebrity endorser gives a positive effect on the image of products and the image of a company. Moreover, the customers also give a positive appreciation to the decision of top management to end a contract with a problematic endorser.Keywords: endorser, advertisement, image